Height changes over subglacial Lake Vostok, East Antarctica: Insights from GNSS observations - Richter, Andreas Jorg (2014)
Height changes of the ice surface above subglacial Lake Vostok, East Antarctica, reflect the integral effect of different processes within the subglacial environment and the ice sheet. Repeated GNSS (Global Navigation Satellite Systems) observations on 56 surface markers in the Lake Vostok region spanning 11 years and continuous GNSS observations at Vostok station over 5 years are used to determine the vertical firn particle movement. Vertical marker velocities are derived with an accuracy of 1 cm/yr or better. Repeated measurements of surface height profiles around Vostok station using kinematic GNSS observations on a snowmobile allow the quantification of surface height changes at 308 crossover points. The height change rate was determined at 1 ± 5 mm/yr, thus indicating a stable ice surface height over the last decade. It is concluded that both the local mass balance of the ice and the lake level of the entire lake have been stable throughout the observation period. The continuous GNSS observations demonstrate that the particle heights vary linearly with time. Nonlinear height changes do not exceed ±1 cm at Vostok station and constrain the magnitude of spatiotemporal lake-level variations. ICESat laser altimetry data confirm that the amplitude of the surface deformations over the lake is restricted to a few centimeters. Assuming the ice sheet to be in steady state over the entire lake, estimates for the surface accumulation, on basal accretion/melt rates and on flux divergence, are derived.